Fluorescence properties of 6-aryl-2′-deoxy-furanouridine and –pyrrolocytidine and their derivatives. (19th December 2017) - Ro, Jong Jin; Go, Gui Han; Wilhelmsson, L Marcus; Kim, Byeang Hyean
Abstract: 2′-deoxyfuranouridine derivatives presenting various aryl groups have been synthesized through Cu(I)-catalyzed intramolecular cyclizations. Moreover, corresponding pyrrolo-dC derivatives have been synthesized and both families of compounds thoroughly characterized using UV/vis and fluorescence spectroscopy as well as time-dependent density functional theory calculations. The photophysical characterization, show that our newly synthesized derivatives of the important pyrrolo-dC family have high fluorescence quantum yields (QYs) and brightness values. Pyrrolo-dC derivative, 3a, shows an environment sensitive QY of up to >60% and brightness of almost 3000, in low polarity solvents and excitation and emission maxima between 365–381 nm and 479–510 nm, respectively, in solvents of different polarities. Two other derivatives, 3b and3c, show high QYs and brightness values of up to 3300 that are fairly insensitive to their microenvironment. These promising photophysical features suggest future applicability as fluorescent nucleobase analogs.